Best Practices in Suicide Pedagogy: A Quantitative Content Analysis - Erin Binkley; Gregory Elliott (Teaching and Supervision in Counseling, 2021)
The authors used a quantitative content analysis methodology to explore the available literature on pedagogical practices for teaching counselors how to work with suicidal clients. From an initial pool of 71 potentially applicable articles found in Counseling, Psychiatry, general mental health, Psychology, and Social Work journals, 26 articles were found to meet inclusion criteria by specifically exploring the impact or efficacy of different pedagogical practices relevant to suicide response in counselor training. These 26 articles were coded using quantitative content analysis procedures. Results indicated that more research is necessary to determine best practices for teaching suicide response to counselors in training. Additionally, these training practices should include attention to the CACREP standards and should be theoretically grounded in pedagogical frameworks. Ideally, future research in this area would focus more heavily on assessment of student competencies and how well students are prepared to respond to suicide.
Keywords: suicide; pedagogy; counselor education; content analysis